Selection of wheat (Triticum aestivum) lines for the high altitude of Indonesia based on single- and multi-character adaptation - YUDIWANTI WAHYU; ELIS NURAENI; TRIKOESOEMANINGTYAS TRIKOESOEMANINGTYAS (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Nuraeni E, Wahyu Y, Trikoesoemaningtyas. 2021. Selection of wheat (Triticum aestivum) lines for the high altitude of Indonesia based on single- and multi-character adaptation. Biodiversitas 22: 5530-5535. The high demand for wheat in Indonesia encourages the assembly of wheat varieties adaptive to the tropical environment. The increase in wheat diversity has been carried out through the crossing process, and it is necessary to evaluate the adaptability of the genotypes resulting from the cross. This study aims to obtain information on the adaptation classes of the F5 population and the differential of agronomic character selection in single and multi-character selection. The study was conducted at the BB Biogen Experimental Garden, Ciwalen (925 masl), in August-December 2020. The F5 of HP1744/Selayar population was used as genetic material with two comparison varieties, namely Guri 1 and Guri 3. The adaptation class for a single character was determined based on seed weight per plant, while for multi-character based on the characters with a wedge between the high category heritability value and the correlation coefficient ?0.5. The result showed that the number of florets, seed weight per plant, number of tillers, number of productive tillers, and weight of seeds in the main panicle were selected as a reference for multi-character selection. The t-test showed that the adaptive and highly adaptive classes genotypes had higher yields than the comparison varieties. The selection differential shows an increase in the mean value for all reference characters. The adaptation class based on a single character resulted in a higher average value of seed weight in all classes compared to selection based on multi-character.